Physik - Sage, Angie; Zug, Mark (New York : Katherine Tegen Books, 2007)
Pulled through a glass that brings him back in time, Septimus Heap becomes the apprentice of an alchemist.
009-up.
Keywords: Apprentices -- Fiction; Magic -- Fiction; Wizards -- Fiction; Time travel -- Fiction; Fantasy fiction